Trans abdominal pre-peritoneal versus totally extra-peritoneal laparoscopic techniques for inguinal hernia repair: a comparative study - Kumar, Praveen; Kumar, Nilkamal (International Surgery Journal, 2016)
Background:Laparoscopic inguinal hernia repair has been controversial as far as the choice of approach is considered. Laparoscopy has obvious advantages over the open technique. TAPP and TEP are the most common laparoscopic approaches. A multitude of research data is available on these, but, evidence based medicine does not allow conclusions to be drawn about the relative effectiveness of TEP compared with TAPP. The scarcity of data about the relative merits and risks of both the methods induced the need to undertake this study. Methods: The study was undertaken for patients admitted in surgery department in a single unit who underwent laparoscopic inguinal hernia repair, either TAPP or TEP, after appropriate patient selection and counseling. 40 patients were assessed in the study between May 2014- May 2016. Results:In our study we found both TAPP and TEP to be safe and feasible options for inguinal hernia repair. TAPP could be the preferred option as it allows visualization and simultaneous repairs of clinically undiagnosed contra-lateral defects. Conclusions:We concluded in this study that laparoscopic inguinal hernia repair may safely be offered to properly selected patients. TAPP and TEP fair equally well in terms of operative time, intra and postoperative complications and patient recovery. TAPP is a better technique as it allows intra-operative diagnosis and repair of previously undiagnosed contra-lateral hernia.